Menakar doktrin Radikalisme dalam Kitab Al-Ushul Ats-Tsalatsah karya Muhammad bin Abdul Wahab: Sebuah analisis kritis : Measuring the Doctrine of Radicalism in the Book of Al-Ushul Ats-Tsalatsah by Muhammad Bin Abdul Wahab: A Critical Analysis - Yusuf Hanafiah; Muhammad Farid Alwajdi; Mohd Izzuddin bin Mohd Pisol; Sutarman Sutarman (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
Today's modern world continues to be faced with the issue of religious radicalism. Communal perception shows that among the pioneers of the modern radicalism movement was Muhammad bin Abdul Wahab. This study aims to identify the existence of the doctrine of radicalism from Muhammad's thought in the book Al-Ushul Ats-Tsalatsah. This research is a qualitative research with the type of library research. The analysis technique in this study uses content analysis and descriptive analysis from various library sources obtained from various references, examined in depth and comprehensively. The primary source in this study is the book Al-Ushul Ats-Tsalatsah by Muhammad bin Abdul Wahab. The secondary references are related manuscripts relevant to this topic. The results of this study show that the content of the book is divided into three points, namely 1) the chapter on fundamental matters that a Muslim needs to know; 2) chapter believing in Allah Almighty; and 3) the urgency chapter on understanding the three essentials of religion. The results of comparative analysis with various previous research, theories, and literature show that the thoughts contained in this book do not show indications of radicalism. The critical analysis of this book is that the pattern of writing or presentation in the book is less systematic.